Teaching practices for creativity at university: a study in Portugal and Brazil - Morais, Maria de Fátima (2017)
Creativity is nowadays seen as an essential feature in higher education. Nevertheless, there is a discrepancy between the need for creativity and what higher education classrooms provide. This study assessed the perceptions of 1599 higher education students from two countries (1059 Brazilian and 540 Portuguese students), from two academic domains (Sciences and Technologies – Sc&T; Social Sciences, Arts, and Humanities – SScA&H), about the presence of creativity in their teachers’ instruction and evaluation practices. The study’s findings evidence interactive effects between the variables country and academic domain for most of the assessed factors: encouragement of new ideas, climate for the expression of ideas, and interest in students’ learning. Brazilian Sc&T students presented more negative perceptions of their classroom environments when compared to SScA&H students; Portuguese students showed opposite patterns of results. Some hypothetical explanations are discussed and future directions for research are presented.